2007
DOI: 10.1037/1064-1297.15.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical verification of smoking status in pregnant and recently postpartum women.

Abstract: The present study was conducted to examine several different methods and cutpoints for determining smoking status in pregnant and recently postpartum women. Self-reported smoking status, urine cotinine levels determined by gas chromatography (GC) and by enzyme immunoassay testing (EMIT), and breath carbon monoxide (CO) levels were assessed at 28 weeks antepartum and 12 and 24 weeks postpartum in 131 women enrolled in studies on smoking cessation and relapse prevention. Classifications based on urine-cotinine G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 22 publications
6
41
0
1
Order By: Relevance
“…Although these data are collected without regard to later cancer, maternal smoking is substantially misclassified on birth certificates (18), which would attenuate relative risks. The remainder of case-control studies of childhood cancers have collected smoking data by maternal interview, raising the possibility of differential reporting between cases and controls, both due to the social disapproval of smoking while pregnant and feelings of culpability among mothers of cases (19). The results of our pilot study suggest that some of these issues may be circumvented by examining the tobacco-specific biomarker cotinine in DBS obtained during the neonatal period and retrieved from storage.…”
Section: Discussionmentioning
confidence: 76%
“…Although these data are collected without regard to later cancer, maternal smoking is substantially misclassified on birth certificates (18), which would attenuate relative risks. The remainder of case-control studies of childhood cancers have collected smoking data by maternal interview, raising the possibility of differential reporting between cases and controls, both due to the social disapproval of smoking while pregnant and feelings of culpability among mothers of cases (19). The results of our pilot study suggest that some of these issues may be circumvented by examining the tobacco-specific biomarker cotinine in DBS obtained during the neonatal period and retrieved from storage.…”
Section: Discussionmentioning
confidence: 76%
“…Las referencias disponibles sobre cotinina urinaria proponen un punto de corte próximo a 80 ng/ml 35 . No obstante, Greaves 36 hace notar que los límites establecidos en la literatura dan lugar a una "zona gris" o de confusión en la que resulta difí-cil interpretar el estatus de fumadora, sobre todo en lo que se refiere a la exposición pasiva o al consumo esporádico.…”
Section: Discussionunclassified
“…However, a recent study of pregnant and postpartum women reported excellent agreement between self-reported smoking status and urinary cotinine measurement. 33 This would fit with the clear dose-related change in the risk of various outcomes from women who had never smoked, those who used to smoke but gave up, and those who smoked throughout their pregnancy reported here. This is encouraging and provides a further reason for pregnant women to stop smoking.…”
Section: Discussionmentioning
confidence: 99%